Особливості визначення професійних та особистісних якостей працівників як параметр прогнозування часу виконання IT-проекту - Сідоркін, Д. В. (ХНУРЕ, 2023)
The report "Features of determining the professional and personal qualities of employees as a parameter for predicting the time for implementing an IT project" discusses the importance of proper personnel selection for the execution of IT projects, as well as methods and tools for assessing professional and personal qualities of employees. The report considers various approaches to assessing staff qualifications and competencies, including the use of assessment tests and competency analysis. Special attention is paid to predicting project implementation time based on personnel quality assessment. The report is intended for managers and managers of IT projects, as well as for anyone interested in effective project management.